Comparative analysis of medical images watermarking methods - Duda, Sylwia; Fijałek, Dominik; Kozieł, Grzegorz (Journal of Computer Sciences Institute, 2020)
The article is devoted to the analysis of watermarking algorithms in terms of their use in marking medical images. The algorithms based on the Integer Wavelet Transform (IWT), Discrete Cosine Transform (DCT), and Singular Value Decomposition (SVD) were compared. The algorithms were implemented using the combinations: IWT, IWT-DCT, and IWT-SVD. As part of the research, the level of disturbances caused by embedding the watermark was checked using subjective and objective methods. The attack resistance of the watermarked images was tested and the steganographic capacity was measured. All algorithms are based on IWT, however, each has different advantages. The algorithm based on the IWT showed the highest capacity. The most resistant to attacks is IWT-SVD, and the lowest level of interference was obtained for the IWT-DCT algorithm.